Dynamics of the Functional State of Students in the Process of Powerliftingin Higher Education - Zhamardiy, Valeriy; Shkola, Olena; Otravenko, Olena; Momot, Olena; Andreieva, Mariia; Andrieieva, Olena; Mudryk, Vasyl; Slusarev, Viktor; Broslavska, Halyna; Putiatina, Halyna (My University, 2021)
The article defines the dynamics of the functional state of students after implementation of methods of special skills and abilities formation during powerlifting classes. It was found that one of the most important tasks of physical education in higher education is the creation of the most favorable, optimal conditions for the harmonious and spiritual development of each student, preservation of student’s health, development of necessary theoretical knowledge, formation of special skills and abilities, maintenance and development of functional capabilities of the organism. We have studied that the formation of a responsible attitude of students to their health is associated with many aspects of the educational process. We have identified that one of the main ways is to cultivate positive, sustainable and effective cognitive interests and students’ understanding of the importance of a healthy lifestyle provided in powerlifting classes
Dynamics of the Functional State of Students in the Process of Powerliftingin Higher Education / Valeriy Zhamardiy, Olena Shkola, Olena Otravenko, Olena Momot, Mariia Andreieva, Olena Andrieieva, Vasyl Mudryk, Viktor Slusarev, Halyna Broslavska and Galina Putiatina // International Journal of Applied Exercise Physiology, 2021. – Vol. 9(10). – P. 24–35
Keywords: методика, пауерліфтинг, студенти, фізична підготовка, фізичне виховання; methods, powerlifting, students, physical fitness, physical education